Nilai Tukar Petani Komoditas Tanaman Pangan Dan Faktor-Faktor Yang Mempengaruhinya Di Provinsi Jawa Barat Tahun 2008 – 2020 - Indra Gunawan; Nataliningsih Nataliningsih; Dety Sukmawati; Agi Dahtiar (Paspalum: Jurnal Ilmiah Pertanian, 2022)
This study aims to analyze the exchange rate of farmers and the factors that influence it in West Java province in 2008 – 2020. The variables studied were land area, rice productivity, fertilizer cost and seed cost. The research method used is the study of literature by examining secondary data published nationally and regionally from various valid and credible sources derived from the Central Statistics Agency, the Department of food crops and Horticulture of West Java Province, the Ministry of Agriculture and others. The study was conducted in the period between November 2021 and March 2022. Data processing is done using Least Squares analysis with the help of E-Views 9 Software. The results showed that the exchange rate of farmers of food crops in West Java Province in the period from 2008 to 2020 was influenced simultaneously by land area, rice productivity, fertilizer cost and seed cost. But partially, the variable land area does not significantly affect the exchange rate of food crop farmers. Variable rice productivity, fertilizer costs and seed costs partially significantly affect the exchange rate of farmers of food crops in West Java.